2015
DOI: 10.1370/afm.1807
|View full text |Cite
|
Sign up to set email alerts
|

Puentes hacia una mejor vida (Bridges to a Better Life): Outcome of a Diabetes Control Peer Support Intervention

Abstract: PURPOSE Peer support can promote diabetes control, yet research on feasible and effective peer support models is lacking. This randomized controlled trial tested a volunteer-based model of peer support for diabetes control.METHODS Thirty-four volunteer peer leaders were recruited and trained to provide support to 5 to 8 patients each through telephone contact, in-person, individual, and group support. Planned dose was 8 contacts, preferably in the first 6 months. Patients with uncontrolled diabetes were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 47 publications
0
39
0
2
Order By: Relevance
“…The results suggest that the difference is the effect of the participation of older adults in community health promotion programs where they receive self-care training to adopt healthy lifestyles and help to strengthen mutual adherence. In this sense, it has been shown that community work and peer support has a positive effect on improving the self-care and health status of adults and older adults (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that the difference is the effect of the participation of older adults in community health promotion programs where they receive self-care training to adopt healthy lifestyles and help to strengthen mutual adherence. In this sense, it has been shown that community work and peer support has a positive effect on improving the self-care and health status of adults and older adults (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…21,26,27,30,37 In contrast, the pooled effect size from the 7 studies with predominantly white, non-Hispanic participants showed no improvement in HbA 1c level with peer support interventions, with an SMD of -0.004 (95% CI, -0.153 to 0.144; P = .95; I 2 = 59.41%). 22,25,29,[31][32][33][34] The pooled effect in the subgroup of 3 studies with predominantly African American participants showed a similar effect size to that seen in the Hispanic subgroup but was not statistically significant, with an SMD of 0.25 (95% CI, -0.064 to 0.571; P = .11; I 2 = 58.60%).…”
Section: Subgroup Analyses Studies With Ethnic or Racial Predominancementioning
confidence: 89%
“…20 Ultimately, 14 articles with RCT designs and 3 cluster RCTs were eligible for inclusion in the meta-analysis, for a total of 4,715 participants. Of the 17 trials, 10 were done in the United States, [21][22][23][24][25][26][27][28][29][30] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Peer support and coaching may offer particular benefits in areas in which health care resources and provider access are lacking. This approach to shared decision making has demonstrated feasibility in varied cultures and settings (Ayala et al, 2015; Safford et al, 2015; Zhong et al, 2015). The World Health Organization has noted that standard features of peer support may be used cross culturally and individual programs can use these features in the development of interventions that best fit the cultures, populations and health systems in which they function (Fisher et al, 2015a).…”
Section: Summary and Critical Review Of The Current State Of Behaviormentioning
confidence: 99%